Annotated Bibliography of Journals and Books on Gender Issues in Serbia 1991–2003 (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This bibliography was initiated as a project of the Center for Women’s Studies in Belgrade in 2003, but remained unfinished until 2018. Its original aim was to present the books and periodicals from the field of feminist studies published in Serbia to feminist theoreticians and activists outside the Yugo-sphere. Individual articles were not included because, in the period presented, there were too many of them for an overview in a single text. Nowadays, this bibliography gives us the insight into the feminist knowledge production in the 1990s in Serbia – the most difficult period in the recent history of Serbia and the whole former Yugoslavia. For new generations, it is a reminder of our efforts to broaden views and to endure in the never-ending struggle.
Keywords: feminism; feminist theory; feminist periodicals; gender studies; Serbia